2001
DOI: 10.1137/s089547980036975x
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Automata Networks and Near Complete Decomposability

Abstract: Abstract. Stochastic automata networks (SANs) have been developed and used in the last fifteen years as a modeling formalism for large systems that can be decomposed into loosely connected components. In this work, we extend the near complete decomposability concept of Markov chains (MCs) to SANs so that the inherent difficulty associated with solving the underlying MC can be forecasted and solution techniques based on this concept can be investigated. A straightforward approach to finding a nearly completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Their investigation suffers from the curse of combinatorial complexity in the same way as the networks considered here. In [16] it is shown that even for loosely coupled systems of automata one has to revert to approximations for computing the steady state distribution of the underlying Markov chains.…”
Section: Related Workmentioning
confidence: 99%
“…Their investigation suffers from the curse of combinatorial complexity in the same way as the networks considered here. In [16] it is shown that even for loosely coupled systems of automata one has to revert to approximations for computing the steady state distribution of the underlying Markov chains.…”
Section: Related Workmentioning
confidence: 99%
“…We remark that the case in which a synchronizing transition probability matrix has zero rows corresponds to an implicit functional dependency between the master automaton of the synchronizing event and the slave automaton whose synchronizing transition probability matrix has zero rows [20]. The reason behind using the reverse of the topological ordering in Definition 4 is the direction of the arcs we choose in G to represent dependencies between automata.…”
Section: Lumpable Partitionings Induced By the Block Structure Of Tenmentioning
confidence: 99%
“…We set C 1 ¼ C 2 ¼ C 3 with values given in column C i . Since the generator has transient states, we first run the state classification (SC) algorithm discussed in [20] to classify the states into recurrent and transient subsets. Columns n r and nz r respectively give the number of recurrent states and the number of nonzero elements in the corresponding submatrix of the generator.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 2 more Smart Citations